Me ajuda com essa equação 5√2 = √(0-1)²+(4-x)²
Soluções para a tarefa
Respondido por
0
espero ter ajudado!!
Anexos:
![](https://pt-static.z-dn.net/files/d72/38b78ae3651112d10291abf15e821852.jpg)
Respondido por
1
Resposta:
x = 4 -√(1 + 5√2)
Explicação passo-a-passo:
5√2 = √(0-1)² + (4-x)² ⇒ 5√2 = √(-1)² + (4-x)² ⇒ 5√2 = -1 + (4-x)² ⇒
1 + 5√2 = (4-x)² , extraindo a raiz quadrada:
√(1 + 5√2) = √(4-x)² ⇒ √(1 + 5√2) = (4-x) ⇒ x = 4 -√(1 + 5√2)
GreenD:
Obrigado!
Perguntas interessantes
Espanhol,
10 meses atrás
História,
10 meses atrás
Português,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Direito,
1 ano atrás